Topical therapy for methicillin-resistant Staphylococcus aureus colonization: impact on infection risk - Robicsek, Ari; Beaumont, Jennifer L; Thomson, Jr, Richard B; Govindarajan, Geetha; Peterson, Lance R (Infection control and hospital epidemiology, 2009)
We evaluated the usefulness of topical decolonization therapy for reducing the risk of methicillin-resistant Staphylococcus aureus (MRSA) infection among MRSA-colonized inpatients. Retrospective cohort study. Three hospitals with universal surveillance for MRSA; at their physician's discretion, colonized patients could be treated with a 5-day course of nasal mupirocin calcium 2%, twice daily, plus chlorhexidine gluconate 4% every second day. MRSA carriers were later retested for colonization (407 subjects; study 1) or followed up for development of MRSA infection (933 subjects; study 2). Multivariable methods were used to determine the impact of decolonization therapy on the risks of sustained colonization (in study 1) and MRSA infection (in study 2). Independent risk factors for sustained colonization included residence in a long-term care facility (odds ratio [OR], 1.8 [95% confidence interval [CI], 1.1-3.2]) and a pressure ulcer (OR, 2.3 [95% CI, 1.2-4.4]). Mupirocin at any dose decreased this risk, particularly during the 30-60-day period after therapy; mupirocin resistance increased this risk (OR, 4.1 [95% CI, 1.6-10.7]). Over a median follow-up duration of 269 days, 69 (7.4%) of 933 patients developed infection. Independent risk factors for infection were length of stay (hazard ratio [HR], 1.2 per 5 additional days [95% CI, 1.0-1.4]), chronic lung disease (HR, 1.7 [95% CI, 1.0-2.8]), and receipt of non-MRSA-active systemic antimicrobial agents (HR, 1.8 [95% CI, 1.1-3.1]). Receipt of mupirocin did not affect the risk of infection, although there was a trend toward delayed infection among patients receiving mupirocin (median time to infection, 50 vs 15.5 days; P=.06). Mupirocin-based decolonization therapy temporarily reduced the risk of continued colonization but did not decrease the risk of subsequent infection.